The Synthesis and Biological Evaluation of 2-(1H-Indol-3-yl)quinazolin-4(3H)-One Derivatives - Mendogralo, Elena Y.; Nesterova, Larisa Y.; Nasibullina, Ekaterina R.; Shcherbakov, Roman O.; Tkachenko, Alexander G.; Sidorov, Roman Y.; Sukonnikov, Maxim A.; Skvortsov, Dmitry A.; Uchuskin, Maxim G. (Molecules (Basel, Switzerland), 2023)
The treatment of many bacterial diseases remains a significant problem due to the increasing antibiotic resistance of their infectious agents. Among others, this is related to Staphylococcus aureus, especially methicillin-resistant S. aureus (MRSA) and Mycobacterium tuberculosis. In the present article, we report on antibacterial compounds with activity against both S. aureus and MRSA. A straightforward approach to 2-(1H-indol-3-yl)quinazolin-4(3H)-one and their analogues was developed. Their structural and functional relationships were also considered. The antimicrobial activity of the synthesized compounds against Mycobacterium tuberculosis H37Rv, S. aureus ATCC 25923, MRSA ATCC 43300, Candida albicans ATCC 10231, and their role in the inhibition of the biofilm formation of S. aureus were reported. 2-(5-Iodo-1H-indol-3-yl)quinazolin-4(3H)-one (3k) showed a low minimum inhibitory concentration (MIC) of 0.98 μg/mL against MRSA. The synthesized compounds were assessed via molecular docking for their ability to bind long RSH (RelA/SpoT homolog) proteins using mycobacterial and streptococcal (p)ppGpp synthetase structures as models. The cytotoxic activity of some synthesized compounds was studied. Compounds 3c, f, g, k, r, and 3z displayed significant antiproliferative activities against all the cancer cell lines tested. Indolylquinazolinones 3b, 3e, and 3g showed a preferential suppression of the growth of rapidly dividing A549 cells compared to slower growing fibroblasts of non-tumor etiology.